Dampak Penyaluran Zakat terhadap Pemberdayaan dan Peningkatan Taraf Hidup Masyarakat Pedesaan - Kamelia, Dina Syaila; Siwi, Mahmudi (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2019)
Empowerment is one of many ways to raise someone’s level to be more confident in applying the skills it possesses. The distribution of zakat maal in the form of business capital loan is one of many forms of sustainable empowerment. Empowerment, in this case, could affect the community’s participation and community’s living standard. The purpose of this research was to identify the impact of empowerment in the distribution of zakat maal in the form of a business capital loan to the community’s participation and living standard using a quantitative approach with survey method. The results of this research showed that empowerment through zakat maal distribution of the mosque succeeded to increase knowledge and awareness of the community about productive zakat so that improved the participation of the community to use business loan service from the baitul maal mosque. The majority of the people who participated in the distribution of zakat maal in this mosque can improve their living standards as income and residential facilities. Keywords: Community empowerment, living standards, zakat maal ABSTRAK Pemberdayaan merupakan salah satu cara untuk mengangkat derajat seseorang untuk lebih percaya diri dalam menerapkan keterampilan yang dimilikinya. Penyaluran zakat maal dengan bentuk pinjaman modal usaha merupakan salah satu bentuk pemberdayaan yang berkelanjutan. Pemberdayaan dalam hal ini dapat berpengaruh terhadap partisipasi dan tingkat taraf hidup masyarakat. Tujuan dari penelitian ini adalah untuk mengidentifikasi dampak pemberdayaan dalam penyaluran zakat maal berupa modal usaha terhadap partisipasi dan tingkat taraf hidup masyarakat melalui pendekatan kuantitatif dengan metode survei. Hasil penelitian ini menunjukkan bahwa pemberdayaan melalui penyaluran zakat maal masjid berhasil meningkatkan pengetahuan dan kesadaran masyarakat mengenai zakat produktif sehingga memunculkan adanya partisipasi masyarakat untuk menggunakan pelayanan pinjaman modal usaha dari baitul maal masjid. Mayoritas masyarakat yang berpartisipasi dalam penyaluran zakat maal masjid ini dapat meningkatkan taraf hidupnya seperti pendapatan, dan fasilitas tempat tinggal.Kata Kunci : Pemberdayaan masyarakat, taraf hidup, zakat maal